Services Marketing Cases in Emerging Markets [electronic resource] : An Asian Perspective - Roy, Sanjit Kumar; Mutum, Dilip S.; Nguyen, Bang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This casebook provides students and academics in business management and marketing with a collection of case studies on services marketing and service operations in emerging economies. It explores current issues and practices in Asia, across different areas, countries, commercial and non-commercial sectors. This book is important and timely in providing a framework for instructors, researchers, and students to understand the service dynamics occurring in these countries. It serves as an invaluable resource for marketing and business management students requiring insights into the operationalization of services across different geographical areas in Asia. Students will find it interesting to compare and contrast different markets covering important aspects related to services.
Service experience and co-creation -- Service branding and Servicescapes -- Transformative services.
Keywords: Business; Marketing; Globalization